Percutaneous biliary intervention for primary sclerosing cholangitis in a patient with situs inversus totalis - Fahrettin KÜÇÜKAY; Rıza Sarper ÖKTEN; Turhan CUMHUR (Turkish Journal of Gastroenterology, 2019)
-